Ethical leadership and environment specific discretionary behaviour: The mediating role of green human resource management and moderating role of individual green values. (24th August 2021) - Islam, Talat; Hussain, Dildar; Ahmed, Ishfaq; Sadiq, Misbah
Abstract: This study examines the mediating role of green human resource management between ethical leadership and employees' citizenship behavior towards the environment with the moderating effect of individual green values. We collected data from 589 MBA executive students with one‐year of experience working in various organizations at two different times using a questionnaire‐based survey method. Applying structural equation modeling to the results confirmed a direct effect of ethical leadership on employees' citizenship behavior towards the environment and an indirect effect through green human resource management. Further, individual green value strengthened the association between green human resource management and employees' environmentally conscious citizenship behavior. Our study contributes to social learning and supply value‐fit theory and has implications for management. Résumé: Les auteurs de cette étude examinent le rôle médiateur de la gestion verte des ressources humaines entre le leadership éthique et le comportement citoyen des employés envers l'environnement, avec l'effet modérateur des valeurs vertes individuelles. Grâce à des questionnaires, les données sont collectées à deux moments différents auprès de 589 étudiants du MBA pour cadres ayant un an d'expérience dans diverses organisations. L'application d'un modèle d'équation structurelle aux résultats confirme l'effet direct du leadership éthique sur le comportement citoyen des employés envers l'environnement et l'effet indirect par le biais de la gestion verte des ressources humaines. En outre, la valeur verte individuelle renforce l'association entre la gestion verte des ressources humaines et le comportement citoyen des employés envers l'environnement. L'étude, qui a des implications pour la gestion, est une contribution à la théorie de l'apprentissage social et de l'adéquation entre l'offre et la valeur.